EVALUATION OF THE ACCURACY OF ANTIDIDIABETIC AGENTS IN PATIENTS WITH DIABETES MELLITUS TYPE II IN THE INPATIENT INSTALLATION OF ONE OF THE PRIVATE AREA HOSPITALS EAST BEKASI 2020 (STIKes Mitra Keluarga, 2021)
Introduction: The selection of appropriate drugs in patients with diabetes mellitus can control the blood sugar levels of a patient. When blood sugar levels can be controlled, then the incidence of complications can be avoided and the numbers of mortality and morbidity in diabetes mellitus will be decreased. The goal of this study is to determine the profile of the use of oral antidiabetic, insulin, or a combination, as well as to assess rationality the use of antidiabetic agents in patients with diabetes mellitus type 2 (DMT2) in the inpatient installation of one of the private hospitals in Bekasi 2020. Method: The research design used was an observational, descriptive, retrospective approach. Data derived from the medical records of DMT2 patients treated as inpatients at a private hospital in Bekasi Timur 2020. Results: Results for profile use of the drug antidiabetic agents most widely used in sequence, i.e., drug combinations of insulin with insulin, oral with oral, and insulin with oral. The evaluation of the accuracy of the use of the drug is set based on four parameters, namely the proper indication of 100%, the right drug of 58,33%, the right of the patient to 100%, and the right dose of 97,62%. Conclusion: It can be concluded that the evaluation of the use of the drug in patients with DMT2 still needs to be done so that the numbers of mortality and morbidity in patients with diabetes mellitus decrease.